Development of Tele Counseling Model in Family Planning Services - Ferina Ferina; Dian Nur Hadianti (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2023)
Background: The impact of the Covid-19 pandemic was truly extraordinary. Not only affecting the health sector or the economy, this outbreak also has an impact on population problems. The decrease in access to health services was not only for ill patients visits, but also the new or old family planning acceptor due to the fear of exposure to illness. Women of childbearing age are predicted to experience unmet need and unwanted pregnancies. This condition was exacerbated by the public's ignorance of accessing family planning counseling services to clinicians/midwives. Therefore, to bridge the needs of prospective family planning acceptors to get assistance in accessing family planning services, a family planning tele-counseling model was developed. Purpose: We aimed to develop a family planning tele-counseling service model. Methods: It was a qualitative study design. Data obtained from snowball sampling technique. Women of reproductive age in the Pasteur subdistrict, Bandung City was interviewed to build themes. The themes obtained were drafted to build a family planning tele-counseling model using a narrative literature review approach. Result: Generated themes that build models of family planning tele-counseling. Conclusion: Family planning tele-counseling was the development of services that were already needed by the community.